2004
DOI: 10.1111/j.1741-2358.2004.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Aged care staff perspectives on oral care for residents: Western Australia

Abstract: Residents face many barriers to maintenance of adequate oral health care, particularly those who are functionally dependent and cognitively impaired. There is an urgent need for appropriate oral care programmes for aged care residents, which include dentists with aged care experience and continuing education for facility staff. Any major programmes should be evaluated carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(83 citation statements)
references
References 21 publications
2
81
0
Order By: Relevance
“…25,28 The present study found that utilization of dental services is strongly influenced by perceived need of oral health treatment and edentulism. Edentulous participants were significantly less likely to visit a dentist in the last 12 months compared to those with natural teeth.…”
Section: Discussionmentioning
confidence: 91%
“…25,28 The present study found that utilization of dental services is strongly influenced by perceived need of oral health treatment and edentulism. Edentulous participants were significantly less likely to visit a dentist in the last 12 months compared to those with natural teeth.…”
Section: Discussionmentioning
confidence: 91%
“…There are major barriers to oral care for older patients in nursing homes that have been reviewed in the United States and Australia [31,32]. The barriers include the lack of specific designated personnel to perform oral care, resident noncompliance with care, and choice of oral care itself.…”
Section: Prevention Of Pneumonia In Elderly Persons: Importance Of Ormentioning
confidence: 99%
“…When, regularly and understandably, nursing home residents fall behind on being able to accomplish their own adequate oral hygiene care, caregivers are supposed to help in adequate tooth brushing and oral hygiene upkeep, but nursing home staff, from aides to physicians, are rarely aware of the importance of and techniques for maintaining oral health care for their patients and consider this among the lowest priorities in their daily patient care 44 . A lack of a specifically designated staff member to perform oral care, along with nonadherence, is cited as a major barrier to adequate oral health care for nursing home residents 45 …”
mentioning
confidence: 99%